Tahlil Indonesia: Solusi Penyatuan Masyarakat Lintas Kelas - Hermanda, Anilla Febriaty; Habibie, M. Rudi (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Tahlil is one of the traditions and cultures of the Indonesian people organized to commemorate the death of a person. This article dissects the benefits and meaning of tahlil to society. Inter-class sentiments within society that occur can be unified through the implementation of tahlil tradition. That is in line with hegemonic analysis which holds that leadership in a group needs awareness to care for one another. The tradition of tahlil has succeeded in uniting the class in society. Classes are formed from social status, occupation, ownership, and so forth. Religious awareness is also awakened through tahlil with the concept of monotheism that is in line with the principle of Belief in the One Supreme God. Besides, tahlil also awaken social awareness of society across the classroom by sitting and eating together, so it can grow the attitude of sympathy and empathy. Tahlil merupakan salah satu tradisi dan kebudayaan masyarakat Indonesia yang diselenggarakan untuk memeringati kematian seseorang. Artikel ini membedah manfaat dan makna tahlil terhadap masyarakat. Sentimen antar kelas di dalam masyarakat yang terjadi dapat disatukan melalui pelaksanaan tradisi tahlil. Hal tersebut sejalan dengan analisis hegemoni yang berpandangan bahwa kepemimpinan dalam sebuah kelompok membutuhkan kesadaran agar saling peduli. Tradisi tahlil telah berhasil menyatukan kelas di dalam masyarakat. Kelas tersebut terbentuk dari status sosial, pekerjaan, kepemilikan, dan lain sebagainya. Kesadaran religius juga terbangun melalui tahlil dengan konsep monoteismenya yang sejalan dengan sila Ketuhanan Yang Maha Esa. Selain itu, tahlil juga membangkitkan kepedulian sosial masyarakat lintas kelas dengan cara duduk dan makan bersama, sehingga dapat tumbuh sikap simpati dan empati.